Lynette Yiadom-Boakye - fly in league with the night - Yiadom-Boakye, Lynette 1977- (Tate, 2020)
Quiet fires: the paintings of Lynette Yiadom-Boakye / Andrea Schlieker -- The power of invention / Isabella Maidment -- Inside the order is always something wild / Elizabeth Alexander -- Five extracts from a detective novel entitled 'An Officer Of The Law' and some intermittent notes on criminality / Lynette Yiadom-Boakye -- Lynette Yiadom-Boakye: Biography and Bibliography -- List of works
Includes bibliographical references and index
Keywords: Yiadom-Boakye, Lynette -- 1977-; Malerei; Person of Color -- Motiv; Yiadom-Boakye, Lynette / 1977- / Exhibitions; Yiadom-Boakye, Lynette; Exhibition catalogs; Ausstellungskatalog -- Tate Britain -- 18.11.2020-09.05.2021 -- London; Ausstellungskatalog -- Moderna Museet -- 12.06.2021-05.09.2021 -- Stockholm; Ausstellungskatalog -- Stiftung Kunstsammlung Nordrhein-Westfalen -- 16.10.2021-13.02.2022 -- Düsseldorf; Ausstellungskatalog -- Musée d'Art Moderne Grand-Duc Jean -- 26.03.2022-04.09.2022 -- Luxembourg; Bildband